Effect of somatic cell count on milk composition and some chemical properties of milk - Safak, T.; Risvanli, A. (FapUNIFESP (SciELO), 2022)
ABSTRACT Subclinical mastitis is a very important disease for dairy cattle farms. As a result of the deterioration of milk quality, it causes economic losses in enterprises. Milk samples of 180 cows were divided into five groups according to the somatic cell count. Some chemical properties and composition were measured in milk samples. The ratio of solid-non-fat, mineral matter, lactose, and protein decreased as the somatic cell count of the milk increased (P˂0.05). No statistical difference was observed between the fat content of milk and the level of somatic cell count (P˃0.05). Although specific gravity decreases (P˂0.05), the electrical conductivity increases (P˂0.001) in milk with high levels of somatic cell count. The milk quality of dairy cattle deteriorates due to the high somatic cell count. Therefore, regular monitoring of somatic cell count is recommended in dairy farms to monitor changes in fat, protein, solid-non-fat, lactose, and mineral matter ratios as well as some chemical properties that make up the milk composition.
Keywords: 2. Zero hunger